Aortic stenosis, angina, and coronary artery disease. Interrelations. - Harris, C N (1975)
Sixty-nine patients over age 35 with severe valvular aortic stenosis were investigated for concomitant coronary artery disease. Forty (57.9%) had clinical angina pectoris. Sixteen (23.2%) had significant coronary occlusive disease by arteriography. Of those with angina, 13 patients (32.5) had significant coronary arterial obstruction, while in the pain-free group only (10.3%) had occlusive coronary disease. It is concluded that patients with severe aortic stenosis who are free of angina have only a small, but definite, chance of having significant coronary disease.